Respuesta :

3x + ky = -1. X=3. Y=5

3x3 + 5k = -1

9 + 5 x -2 = -1

9 + -10 = -1
In these type of questions, we have to substitute the numbers given into the algebraic expression.

when 3x + ky = -1,
and x=3 and y=5, 
we can write this equation to solve for k:
3(3) + k(5) = -1

to solve this, first simplify the numbers.
9 + 5k = -1
shift +9 to the other side and turn it into -9
5k = -1 -9
5k = -10
shift x5 to the other side and turn it to ÷5
k = -10 ÷ 5
k = -2

So the answer is E :)

ACCESS MORE